Implementation Of Da'wah Management Function In Improving The Quality Of Worship Of The Mursyid Al Ikhwan Taklim Council In Bandar Khalipah Village, Percut Sei Tuan District - Nurhaliza Salsabila; Erwan Efendi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This research is motivated by changes in the quality of congregational worship in the Taklim Council of Mursyid Al Ikhwan, which emphasizes the importance of implementing da'wah management in a structured manner. This study aims to examine the implementation of the da'wah management function in an effort to improve the quality of congregational worship. The method used is qualitative research with a descriptive approach, through data collection techniques such as observation, interviews, and documentation. The results of the study show that the da'wah management function in planning, organizing, implementing, and evaluating has been applied quite systematically, although it is still simple and flexible. The supporting factors include the existence of financial support, active participation of the congregation, and a conducive social environment, while the inhibiting factors include the instability of attendance and limited time of the congregation. The implementation of da'wah management has a positive impact on improving the quality of worship, both in terms of understanding, implementation, and social behavior of the congregation. Thus, the consistent implementation of the da'wah management function makes a significant contribution to improving the quality of congregational worship.